68.9k views
5 votes
Evaluate this expression when c= -2 and d= 2:

Evaluate this expression when c= -2 and d= 2:-example-1

2 Answers

3 votes

Explanation:

you just have to put the given values in place of the variable names and then simply calculate.

(-2² + 2²) - 2(-2² - 2²) = (4 + 4) - 2(4 - 4) = 8 - 2×0 = 8

so, B is the right answer.

please remember the correct sequence of operations :

first are brackets.

then exponents.

then multiplications and divisions.

and then (at last) additions and subtractions.

and also please remember : multiplying a negative number with a negative number creates a positive result.

that is of course also true for squaring a negative number, as ² just means that the negative number is multiplied with itself.

now you also know the result of -2³, right ?

as this means -2 is multiplied 3 times by itself. what does that do to the sign ?

-2 × -2 = 4 (positive).

but now we have to multiply a third time

4 × -2 = -8 (because multiplying a positive number with a negative number creates a negative result).

User LLuz
by
4.9k points
2 votes
B. 8
refer to steps for answer!
User Tromgy
by
5.3k points